Action at a distance: dependency sensitivity in a New World primate - Andrea Ravignani; Ruth Sonnweber; Nina Stobbe; W. Tecumseh Fitch (2013)
Sensitivity to dependencies (correspondences between distant items) in sensory stimuli plays a crucial role in human music and language. Here, we show that squirrel monkeys (Saimiri sciureus) can detect abstract, non-adjacent dependencies in auditory stimuli. Monkeys discriminated between tone sequences containing a dependency and those lacking it, and generalized to previously unheard pitch classes and novel dependency distances. This constitutes the first pattern learning study where artificial stimuli were designed with the species' communication system in mind. These results suggest that the ability to recognize dependencies represents a capability that had already evolved in humans' last common ancestor with squirrel monkeys, and perhaps before.